Development of vegan hamburger added from leaf cabbage flour: physical-chemical, microbiological and sensory evaluation (Research, Society and Development, 2021)
In a constant rise, the number of people adept at veganism imposes on the market diversified food alternatives, therefore, it is of great importance the development of foods with formulations that aim at the substitution of animal meat material by plant origin. Thus, the use of jackfruit as a basis for making a hamburger can be shown as a nutritional and socioeconomic potential. The objective was to elaborate and carry out physical-chemical, microbiological, sensory and performance analyzes on “jackfruit” hamburgers added with a mix of flours from the seed of the fruit and the cabbage leaf. Immature jackfruits of the “hard” variety were selected. After cleaning and sanitizing, part of the fruit was heat treated in the oven for subsequent separation of the pulp and seed, which was frozen and transformed into flour, respectively, as well as in the fresh portion. Then, after elaboration, the two hamburger formulations were subjected to the aforementioned analyzes, and in the sensory evaluation the samples were subjected to a thermal process and thus 60 tasters performed acceptance test on a 9-point hedonic scale and purchase intention. At the end of the research, the product showed no physical-chemical differences, showed good microbiological characteristics and obtained good sensory acceptance for the HV01 sample, showing the potential to be a good collaboration with the food industry, thus offering a more marketing option for the growing number of vegan individuals.